Tinjauan Historis Kurikulum Pesantren Sirajul Huda Kabupaten Karo - Muhammad Irsan Barus; Syadidul Kahar (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2019)
AbstractIslamic education is an education based on the value of Islamic teachings contained in the Qur'an and the hadith as well as the thinking of scholars in the history practice of Muslims. The process of Islamic education continues to grow thanks to traders and preachers all over Indonesia including North Sumatra. The history of Islamic education in the Karo Land begins with the Islam of the family of Sulaiman Tarigan. Sulaiman Tarigan's awareness of Islamic education motivated him to prepare a successor cadre for the Islamic development struggle. The work of preparing the cadres was established by establishing the Three Beringin School in 1925. The study expanded rapidly until the school moved to Kuala Baru and started the establishment of Sirajul Huda boarding school in 1994. In addition they learn to read and write the Koran and Malay. Keywords: History, Islamic Education, Karo Land